LOAN WORDS IN INDONESIAN - Rina Devianty (UIN Sumatera Utara, 2016)
This article describes the contribution of some foreign language vocabulary in Indonesian. In the loan of foreign language vocabulary into the Indonesian, remains to be adjusted with the writing and pronunciation Indonesian. One foreign language is absorbed into the Indonesian language is English.Keyword: loan, foreign language, English